Politicizing the International Criminal Court : the convergence of politics, ethics, and law - Roach, Steven C. (Lanham : Rowman & Littlefield Publishers, 2006)
This innovative and systematic work on the political and ethical dimensions of the International Criminal Court (ICC) is the first comprehensive attempt to situate the politics of the ICC both theoretically and practically. Steering a new path between conventional approaches that stress the formal link between legitimacy and legal neutrality, and unconventional approaches that treat legitimacy and politics as inextricable elements of a repressive international legal order, Steven C. Roach formulates the concept of political legalism, which calls for a self-directed and engaged application of t.
History and legal structure -- Historical background : from the League of Nations to the Rome conference -- Legal principles and political issues -- Theory and ethics -- Legalization, pragmatic ethics, and integration -- Constructing world society : the ethics and politics of global juridification -- Value pluralism, liberalism, and political cosmopolitanism -- Political legalism : political strategies and policy arrangements -- U.S. opposition and strategic accommodation -- Religion and politics : Arab states and the role of Islam ethics -- A cooperative arrangement with the U.N. Security Council -- Conclusion : toward a new global political order.
Includes bibliographical references (pages 191-206) and index.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Keywords: International Criminal Court; International Criminal Court; International criminal courts -- Moral and ethical aspects; International criminal courts -- Political aspects; International cooperation; Law -- Criminal Law -- General; International cooperation